An Environmental Management Experience Within the Project: Improvement of Educational Opportunities in Rural Environmental Management in Sarapiqui and Guapiles’ Schools - Giselle León-León (Revista Electrónica Educare)
A very important aspect of worldwide education and, particularly for Costa Rican education, is the environmental management as an educational strategy. For this reason, this article describes the experience of the project Mejora de la Oferta Educativa en Gestión Ambiental Rural (MOE-GAR) during its first stage in 2009. The population was comprised by teachers from different areas of the rural school districts of Guapiles and Sarapiquí. As a part of this project, we worked with teachers, different government and nongovernment institutions, throughout the 2009 school year; obtaining as a result, a process of knowledge development in environmental management. Based on this, several proposals were developed in different educational institutions.